Bridging the digital divide: how internet access shapes human capital development and economic inequality - Liao, Jinyan; Sameer Kumar; Furuoka, Fumitaka (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study investigates the relationship between the digital gap and the development of human capital concerning economic inequality. Despite the swift progression of the digital economy, which presents novel chances for knowledge acquisition and skill development. The unequal access to the internet has deepened disparities in human capital across different socioeconomic groups, thereby contributing to broader economic inequality. The digital divide is primarily influenced by a combination of factors: access to technology, digital literacy, and financial circumstances. We examine specific regions and demographic groups to analyze the impact of digital skills on human capital development and employment opportunities in countries with differing economic statuses. The primary finding of the studies indicates that, particularly in disadvantaged regions, digital literacy significantly enhances individuals' economic mobility. To ensure equitable access for marginalized populations, it presents policy recommendations centered on targeted educational reforms in digital literacy and infrastructure investments to bridge the digital gap. Based on these findings, policymakers should prioritize creating inclusive digital education programs and improving internet accessibility in rural areas to reduce economic disparities. These insights include strengthening digital education policies and prioritizing internet infrastructure in marginalized areas, aiming to narrow socioeconomic disparities.